Legal Implication of the Amendment to Cooperative Regulation in Omnibus Law Draft Bill on Job Creation - Widiastuti Widiastuti (Universitas Slamet Riyadi, 2020)
The Draft Bill on Job Creation aiming to encourage investment to open job opportunity has amended several laws to be harmonized. One of parts amended by the Draft Bill on Job Creation is Cooperative Law. In the Draft Bill on Job Creation, there are 4 articles of Cooperatives Law amended, i.e. the establishment of cooperatives can be conducted by 3 persons, the presence of members in Members Meeting can use representative system, the number of members can be recorded electronically, and the cooperatives is operated based on sharia principle. The amendment to 4 Articles of Cooperatives Law has implication to the amendment to other articles. The implication can be an imperative related to the presence of clear regulation about members, administrators, and cooperatives supervisors’ responsibility in both conventional and sharia-based cooperatives, the members of which consisted of 3 persons, and the regulation of cooperatives member meeting organization with representative system.